Statins in Depression: An Evidence-Based Overview of Mechanisms and Clinical Studies - De Giorgi, Riccardo; Rizzo Pesci, Nicola; Quinton, Alice; De Crescenzo, Franco; Cowen, Philip J.; Harmer, Catherine J. (Frontiers in Psychiatry, 2021)
Background: Depression is a leading cause of disability, burdened by high levels of non-response to conventional antidepressants. Novel therapeutic strategies targeting non-monoaminergic pathways are sorely needed. The widely available and safe statins have several putative mechanisms of action, especially anti-inflammatory, which make them ideal candidates for repurposing in the treatment of depression. A large number of articles has been published on this topic. The aim of this study is to assess this literature according to evidence-based medicine principles to inform clinical practice and research. Methods: We performed a systematic review of the electronic databases MEDLINE, CENTRAL, Web of Science, CINAHL, and ClinicalTrials.gov, and an unstructured Google Scholar and manual search, until the 9th of April 2021, for all types of clinical studies assessing the effects of statins in depression. Results: Seventy-two studies were retrieved that investigated the effects of statins on the risk of developing depression or on depressive symptoms in both depressed and non-depressed populations. Fifteen studies specifically addressed the effects of statins on inflammatory-related symptoms of anhedonia, psychomotor retardation, anxiety, and sleep disturbances in depression. Most studies suggested a positive effect of statins on the occurrence and severity of depression, with fewer studies showing no effect, while a minority indicated some negative effects. Limitations: We provide a narrative report on all the included studies but did not perform any quantitative analysis, which limits the strength of our conclusions. Conclusions: Robust evidence indicates that statins are unlikely to lead to depressive symptoms in the general population. Promising data suggest a potential role for statins in the treatment of depression. Further clinical studies are needed, especially in specific subgroups of patients identified by pre-treatment assessments of inflammatory and lipid profiles.